An empirical-deductive model for the assessment of the mortgage lending value of properties as securities for credit exposures. Issue 1 (8th May 2018) - Tajani, Francesco; Morano, Pierluigi
Abstract : Purpose: This study aims to propose and test an innovative methodology for assessing mortgage lending value. The method tries to improve and rationalize, within the canonical and derivative approach that is generally used by the sector operators, the appraisal of the percentage reduction to be applied to the market value. Design/methodology/approach: Considering that the European Mortgage Federation and the Basel Committee highlight the importance of information about the risks of properties to be loaned on, the value at risk approach has been developed so as to assess the mortgage lending value as a technique of risk analysis. With reference to the Italian context, the method elaborates the historical analysis of the property values in 93 major Italian cities for the residential and commercial intended uses in a significant period (1967-2015) and allows to determine the reduction coefficients of the market value as a function of the central, semi-central and peripheral locations of the property. Findings: The results include the reduction coefficients of the market value for the derivative appraisal of the mortgage lending value. The coefficients obtained satisfy the need for a rational assessment of the property risk and the appropriate spatial contextualization of the risk components related to the local demand and supply, thus eliminating any inconsistency and danger of determining the mortgage lending value using a simple and lump-sum percentage deduction of the market value. Originality/value: The global economic crisis in the past decade, triggered by the 2007 US Subprime mortgage crisis and consequent collapse of property values, has highlighted the need for high level professional skills in the appraisal of properties as securities for credit exposures. The method proposed for the assessment of the mortgage lending value allows to overcome the uncertainties underlying the determination of an independent value through indirect methods (income approach, cost approach) and rationalize the appraisal of the risk in the traditional derivative approach through a flexible procedure, with it being possible to adapt it to any territorial context, as well as any intended use.